Yolk–shell nanoarchitecture for stabilizing a Ce2S3 anode. Issue 5 (15th July 2021) - Hui, Kanglong; Fu, Jipeng; Liu, Jie; Chen, Yongjin; Gao, Xiang; Gao, Tian; Wei, Qi; Li, Chengyu; Zhang, Hongjie; Tang, Mingxue
Abstract: Rare‐earth sulfides are of research interest for lithium‐ion batteries (LIBs) due to their abundant lithium intercalation sites and low redox voltage. However, their electrochemical performances are not satisfactory because of poor conductivity and volume change upon electrochemical cycling. Herein, nanoarchitectures of γ‐Ce2 S3 encapsulated in a hollow mesoporous carbon nanosphere (Ce2 S3 @HMCS) are fabricated using the self‐template strategy combined with the in‐sphere sulfuration method and tested as an LIB anode. The void space between the Ce2 S3 core and the outer layer of the carbon nanosphere has been properly designed and modulated to achieve excellent electrochemical performance in terms of electronic conductivity, reversibility, and rate capability. The reversible capacity of Ce2 S3 @HMCS is 2.6 times that of the pure Ce2 S3 anode, which can gradually increase and maintain a capacity of 282 mAh·g −1 at a current density of 1 A·g –1, and a high Coulombic efficiency (~100%) can be achieved even after 1000 cycles. This good performance is attributed to the unique yolk–shell nanostructure with a highly crystallized and stable Ce3 S2 core and volume expansion buffer space upon lithiation/delithiation. Ex situ X‐ray diffraction and nuclear magnetic resonance results indicate that the lithiation of Ce2 S3 @HMCS is an intercalation process. This study represents an important advancement in precise structural design with in‐sphere sulfuration and sheds light on a potential direction for high‐performance lithium storage. Abstract : The Stöber sol–gel method with the in‐shell sulfuration approach crafts yolk–shell γ‐Ce2 S3 in hollow mesoporous carbon nanospheres of Ce2 S3 @HMCS, offering enhanced electronic conductivity and voids for increasing structural stability when compared with untreated Ce2 S3 . The strategy of in situ fabrication of nanoarchitecture expands upon the methods available to design energy storage materials.